How race is made : slavery, segregation, and the senses - Smith, Mark M. (Mark Michael), 1968- (The University of North Carolina Press, 2006)
Offers an analysis, extending from the colonial period to the mid-twentieth century, that shows how whites of all classes used the artificial binary of "black" and "white" to justify slavery and erect the political, legal, and social structure of segregation